Incidence of aspirin resistance is higher in patients with acute coronary syndrome and atrial fibrillation than without atrial fibrillation - Baş,Hasan Aydin (2020)
SUMMARY In patients with atrial fibrillation, standard anticoagulation with a vitamin K antagonist plus dual antiplatelet therapy with a P2Y12 inhibitor and aspirin is the standard of care after percutaneous coronary intervention (PCI). While this therapy reduces the risk of thrombosis and stroke, it increases the risk of bleeding. It is unclear whether the antiplatelet effect of aspirin and clopidogrel may worsen atrial fibrillation (AF). OBJECTIVE Thus we aimed to analyze platelet aspirin resistance (AR) and clopidogrel resistance (CR) in acute coronary (ACS) patients based on sinus rhythm (SR) and AF. METHODS In this prospective trial, we included 543 patients (mean age: 62± 12 years; range: 26 - 89 years) who were on aspirin and clopidogrel therapy after the diagnosis of acute coronary syndrome. AR and CR were analyzed by a Multiplate® MP-0120 device by using the method of whole blood aggregometry. RESULTS AF patients had significantly higher age, mean platelet volume, and High-Sensitivity C-Reactive Protein (p< 0.01 for each parameter). Similarly, Arachidonic-acid induced (ASPI) aggregation was higher in AF patients compared to SR patients (666±218 vs. 187±179, p<0.001). Among the ACS patients, significantly more female patients had AF (p<0.001). The incidence of hypertension in the AF group was higher compared to the SR group (p<0.001). However, adenosine diphosphate levels were not at a significant level in the two groups. CONCLUSION Our findings indicate that the platelet inhibitory effect of Aspirin was worse for patients with AF, suggesting that the effectiveness of aspirin may be less in the prophylaxis of thromboembolism and more a bleeding risk.